Enhancing School Effectiveness by Implementing Identified and Intrinsic Motivation Among Primary School Teachers - Khun-Inkeeree, Hareesol; Yusof, Mat Rahimi; Maruf, Irma Rachmawati; Mat, Tuan Roslina Tuan; Sofian, Fatimah Noor Rashidah Mohd (Frontiers in Education, 2022)
Teacher job motivation is one of the factors that influence school effectiveness. The success of a school can be seen in the achievement of outstanding results and the absence of disciplinary difficulties. As a result, this research was carried out with the aim of identifying the dimensions that affect teachers' job motivation and school effectiveness in Pasir Mas District Excellence Cluster Primary School, Kelantan. A cross-sectional sampling approach was used in this report, with a questionnaire distributed to 146 teachers from four primary schools in the Pasir Mas district. According to the findings of a study conducted with SEM-PLS, the identified motivational dimensions and intrinsic dimensions for teacher job motivation independent variables are predictors of school effectiveness contingent variables in Pasir Mas District Excellence Cluster Primary School. The study's implications show that teacher job motivation is significant in attempts to increase school effectiveness. Teachers now play an important part in education by improving the effectiveness of teaching and learning in classrooms. This is seen as very important to maximize student achievement as well as increase the effectiveness of the school because excellent and high -performing students are the result of an effective institution.